Trading Frequency in KSE – 100 Index Using Pastor and Stambaugh Model - Ahmed, Farhan; Ali, Mudassir; Raza, Muhammad; Sibghat, Muhammad (UI Scholars Hub, 2019)
The study aims to asses Pastor & Stambaugh model on Pakistan Stock Exchange (KSE-100 Index) from 2007 to 2017. Four commonly asset pricing factors are tested including market risk, size, value and liquidity premium. Except for the value premium, all factors are statistically found significant. Pertinent to mention that liquidity factor is initially found insignificant since annual returns are calculated. However, after taking most liquid sector during the period (Chemical Sector) the liquidity measure is derived through monthly returns. The result of the study is backed with Utility preference theory because it is observed that investors do prefer more liquid stocks and as a result when pricing securities liquidity factor holds an important position.